Unveiling the dual nature of Lactobacillus: from cariogenic threat to probiotic protector—a critical review with bibliometric analysis - Di Fu; Xingyue Shu; Lin Yao; Ge Zhou; Mengzhen Ji; Ga Liao; Yunwo Zhu; Ling Zou (Frontiers in Oral Health)
IntroductionDental caries is a prevalent oral disease with a multifactorial etiology. Lactobacillus has been implicated in caries progression on account of its acidogenic properties; On the other hand, they constitute one of the potential probiotic strategies for preventing dental caries. This complex relationship renders the relationship between Lactobacillus and dental caries remains ambiguous.MethodsThe Web of Science core collections (WoSCC) were searched to acquire articles relevant to Lactobacillus and dental caries. After retrieval and manual screening, publications were analyzed by VOSviewer.ResultsSweden, the US, and China, which have been the center of international cooperation, have produced the most publications in the research area. Caries Research is the main counterpart journal in the field. “Dental caries”, “Streptococcus mutans”, “Lactobacilli”, “Probiotics”, and “Children” have been commonly used as keywords.DiscussionBased on bibliometric analysis, this study reviews the relationship between lactobacilli and dental caries, emphasizing their dual roles. The detection rate of lactobacilli is closely associated with the incidence and severity of dental caries. However, under specific environmental conditions, these bacteria also exhibit potential probiotic properties that may aid in the prevention of dental caries. Additionally, Lactobacillus is strongly associated with early childhood caries, a specific type of caries.